The Influence Of Product Quality, Price, And Promotion And Their Relationship To Consumer Decisions In Buying Queen Accessories Products In The City Of Surakarta - Adisa Fusanita; Mrihrahayu Rumaningsih; Kurniawati Darmaningrum (Journal of Rural and Urban Community Studies, 2023)
This study aims to determine: (1) The effect of quality on consumer decisions in purchasing queen accessories products in the city of Surakarta, (2) To determine the effect of price on consumer decisions in buying queen accessories products in the city of Surakarta, (3) To determine the effect of promotion on consumer decisions in buying queen accessories products in the city of Surakarta, and lastly, (4) To find out whether the three variables together influence consumer decisions in buying queen accessories products in the city of Surakarta. The method used in this research is a survey method by distributing questionnaires. The technique used is purposive sampling. Samples taken as many as 100 respondent. The data analysis used was multiple linear regression analysis using the SPSS version 22 application. This study (1) partially product quality has a positive and significant influence on buying decisions with a Beta value of 27%. (2) partially the price of the product has a positive and significant influence on buying decisions with a Beta value of 25%. (3) partially promotion has a positive and significant influence on buying decisions with a Beta value of 31%. (4) simultaneously quality, price, and promotion have a positive and significant effect on purchasing decisions, with an F value of 2.70 and Sig. 0.000, so that 34.508 > 2.70 is obtained and the value of Sig. 0.000 < 0.05